Retrograde and Direct Wave Locomotion in a Photosensitive Self‐Oscillating Gel. (13th October 2016) - Ren, Lin; She, Weibing; Gao, Qingyu; Pan, Changwei; Ji, Chen; Epstein, Irving R.
Abstract: Crawling motion mediated by retrograde and direct waves, that is, in the opposite or the same direction, respectively, as the muscular wave that generates it, is a fundamental mode of biological locomotion, from which more complex and sophisticated locomotion modes involving outgrowths such as limbs and wings may have evolved. A detailed general description of muscular wave locomotion and its relationship with other modes of locomotion is a challenging task. We employ a model of a photosensitive self‐oscillating gel, in which chemical pulse waves and a stimulus‐responsive medium play roles analogous to nerve pulses and deformable muscles in an animal, to generate retrograde and direct waves under non‐uniform illumination. Analysis reveals that the directional locomotion arises from a force asymmetry that results in unequal translation lengths in the push and pull regions associated with a pulse wave. This asymmetry can be modulated by the kinetic parameters of the photosensitive Belousov–Zhabotinsky reaction and the performance parameters of the gel, enabling a transition between retrograde and direct wave locomotion.